God's Mission as Praxis for Healing and Reconciliation - Isaak, Paul John (International review of mission, 2011)
In the first part I address the missional church and its praxis: what God in Jesus Christ together with the Holy Spirit is doing in the world to bring about healing, reconciliation, wholeness, liberation and salvation. In the second section I address the issue of healing from contextual and holistic perspectives. The third part is on reconciling mission and mission as reconciliation. Mission as reconciliation should continually seek to correspond to the specifics of a given context. In short, God's mission as praxis for healing and reconciliation means serving, healing, and reconciling a wounded and broken humanity.